Enhancing Attractiveness Through Adaptive Re-Use: A Critical Literature Review - Arie Infanto; Nurlisa Ginting; Achmad Nasution (Talenta Publisher, 2026)
This paper presents a critical literature review examining the role of adaptive re-use in enhancing the attractiveness of cultural heritage buildings and historically significant environments. Drawing on peer-reviewed publications published between 2019 and 2025, the study synthesis recent theoretical discussions and empirical findings related to key dimensions of attractiveness, including authenticity, historical and cultural value, aesthetics, accessibility, and sustainability. Rather than adopting a case-based analytical approach, this paper critically evaluates contemporary conceptual frameworks, methodological approaches, and ongoing scholarly debates within adaptive re-use and heritage tourism studies. By doing so, the review aims to identify existing research gaps and propose directions for future research in the field.